2019
DOI: 10.1007/s11664-019-07049-1
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Microwave Materials: A Review

Abstract: The performance of microwave devices mainly depends on the properties of materials used in the fabrication. Knowledge of material properties at microwave frequencies is a prerequisite to select suitable materials for various microwave applications and vice versa. In this review, seven categories of materials and their applications in a microwave regime are elaborately discussed. The categories include magnetic materials, carbon-based materials, flexible or stretchable materials, biomaterials, phantoms, tunable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
63
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(78 citation statements)
references
References 187 publications
0
63
0
4
Order By: Relevance
“…While, glass is a good thermal and homogeneity insulator, it also displays a high dielectric loss 28 . To obtain a lower α d value and maintain the advantages of glass, glass-reinforced ceramics can be used as displayed by R04350 28 . In any event, the dielectric loss of R04350 is still higher than RT5880, TMM4 and RT6010.…”
Section: Andmentioning
confidence: 99%
“…While, glass is a good thermal and homogeneity insulator, it also displays a high dielectric loss 28 . To obtain a lower α d value and maintain the advantages of glass, glass-reinforced ceramics can be used as displayed by R04350 28 . In any event, the dielectric loss of R04350 is still higher than RT5880, TMM4 and RT6010.…”
Section: Andmentioning
confidence: 99%
“…In case of significant EMI in the circuitry, several methods can be employed to enhance the immunity of the system such as enhancing the shielding effectiveness using various conductive materials or microwave absorbers, 9,10 making use of EMI filters, 11,12 optimizing the layout of the circuit 13 etc.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that microwave sintering can greatly shorten the sample preparation process and accelerate crystal growth. This occurs mainly owing to non-thermal and thermal microwave effects [ 2 , 3 , 4 ]. The thermal microwave effect is mainly manifested in differences in thermodynamics, including problems such as faster heating rates and local hot spots [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%